Descriptive Study of Teachers’ Perceptions in Using Merdeka Curriculum in Teaching English - Blongkod, Adhe Liani; Pilongo, Jolanda Hulda Debora; Napu, Novriyanto (Transbahasa, 2023)
This recent research aimed to describe teachers’ perceptions in using Merdeka Curriculum in teaching English in SMA Negeri 3 Gorontalo Utara and SMA Negeri 5 Gorontalo Utara. The method of this research was qualitative design that is hoped to give detail and in-depth information about certain phenomenon. the result of research showed teachers positively perceive the Merdeka Curriculum's structure, commending its flexibility in organizing intracurricular content to cater to diverse student needs through innovative approaches. The division of teaching hours into intracurricular and Pancasila strengthening is also acknowledged. Implementation strengths include flexible teaching models, student-centered learning, and school autonomy. Challenges include effective teaching hour allocation, adapting to new terminology, and the need for continuous support, especially in English learning. Regarding the Pancasila Students' Profile, teachers appreciate the multifaceted approach to character education, emphasizing practical application over theoretical understanding. The early stages of the P5 program show promise in integrating Pancasila values, yet challenges persist in students' character attitudes and the call for enhanced collaboration.